Management of long bone non-unions and implant failures utilizing the diamond concept: a retrospective case series - Shah, Kashish M.; Tijoriwala, Prabhav P.; Rathod, Janak A.; Patel, Dhruv M.; Makwana, Pratik H. (International Journal of Research in Orthopaedics, 2026)
The management of long bone non-unions and implant failures remains a significant orthopaedic challenge, imposing a substantial socio-economic burden on both the patient and the healthcare system. The "Diamond Concept" provides a comprehensive framework to address these complex scenarios by simultaneously optimizing mechanical stability and the biological healing environment. This study aims to evaluate the clinical and functional outcomes of recalcitrant non-unions treated according to this concept. A retrospective case series was conducted at a tertiary care center (SMIMER, Surat) between 2024 and 2026. Eighteen patients presenting with aseptic, infected, atrophic, or hypertrophic non-unions, as well as mechanical implant failures, were included. Treatment strategies were individualized to restore the physiological elements of fracture healing via revision osteosynthesis (single/dual plating or prosthesis) and biological augmentation (autologous bone grafting). The cohort consisted of 12 males and 6 females, with a mean duration of 7 months between the index surgery and revision. Ten cases involved the upper limb and eight involved the lower limb. Revision procedures utilized single implants (n=9), dual implants (n=7), and prosthetic replacements (n=2). Bone grafting was required in 13 cases. All followed patients achieved or are progressing toward solid clinical and radiological union, with a mean return-to-work time of 9 months from the index surgery. Precise identification of the etiology behind primary fixation failure is crucial. Adherence to the Diamond Concept through tailored mechanical stabilization and biological augmentation yields excellent union rates and functional recovery in complex non-unions.